2019
DOI: 10.1016/j.neuropharm.2019.107743
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin 5-HT1A, 5-HT2A and dopamine D2 receptors strongly influence prefronto-hippocampal neural networks in alert mice: Contribution to the actions of risperidone

Abstract: Atypical antipsychotic drugs (APDs) used to treat positive and negative symptoms in schizophrenia block serotonin receptors 5-HT 2A R and dopamine receptors D 2 R and stimulate 5-HT 1A R directly or indirectly. However, the exact cellular mechanisms mediating their therapeutic actions remain unresolved. We recorded neural activity in the prefrontal cortex (PFC) and hippocampus (HPC) of freely-moving mice before and after acute administration of 5-HT 1A R, 5-HT 2A R and D 2 R selective agonists and antagonists … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 61 publications
4
34
0
Order By: Relevance
“…6a,b). Notably, a prior study we conducted showed that DPAT given alone, in the absence of PCP, suppressed the power of high gamma and HFOs in both the PFC and HPC and such decreases were reversed by the selective 5-HT 1A R antagonist WAY-100635 (PFC high gamma, HFO: F 1,6 = 10, 9.12 p = 0.003, 0.001; HPC high gamma, HFO: F 1,6 = 12.45, 21.66 p = 0.003, 0.001; one-way ANOVA; n = 7 mice)(Gener et al, 2019). This indicates that 5-HT 1A Rs indeed play a role in shaping high gamma and HFO within the PFC and the HPC.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…6a,b). Notably, a prior study we conducted showed that DPAT given alone, in the absence of PCP, suppressed the power of high gamma and HFOs in both the PFC and HPC and such decreases were reversed by the selective 5-HT 1A R antagonist WAY-100635 (PFC high gamma, HFO: F 1,6 = 10, 9.12 p = 0.003, 0.001; HPC high gamma, HFO: F 1,6 = 12.45, 21.66 p = 0.003, 0.001; one-way ANOVA; n = 7 mice)(Gener et al, 2019). This indicates that 5-HT 1A Rs indeed play a role in shaping high gamma and HFO within the PFC and the HPC.…”
Section: Resultsmentioning
confidence: 99%
“…Sedation has been attributed to APDs’ affinity for histamine H 1 receptors (Miller, 2004). However, a recent study from our group also indicated that sedative effects may result from the cooperation between 5-HT 2A /D2R antagonism and 5-HT 1A agonism (Gener et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We recorded single-unit activity (SUA) and local field potentials (LFPs) with the Open Ephys system with a sampling rate of 30 kHz. We used the accelerometer's signals to monitor general mobility of mice (65). SUA was estimated by referencing the signal, filtering between 450 and 6,000 Hz and sorting the spikes with Offline Sorter.…”
Section: Summary Of Methodsmentioning
confidence: 99%